332 THE PATIENT EXPERIENCE OF THE OLDER PERSONS REHAB AT HOME (OPRAH) SERVICE. (25th October 2022) - Murphy, R; Doyle, E; O'Connor, A; Coen, M; Connolly, A; Breen, C; Carty, J; Waters, R; Canavan, M; Robinson, S
Abstract: Background: The Older Persons Rehab at Home (OPRAH) team is a novel service developed to provide patients with intensive domiciliary based therapy to regain function, mobility and social care goals. This provides rehabilitation in the patients' own home and accelerates discharge from the acute care sector. In this study patient and carer experiences of the service were explored. Methods: Patients were sent a postal questionnaire after discharge from the service to collect information on the patient experience of the OPRAH service. The following measures were collected: satisfaction with the service, experience of interacting with therapy staff, involvement in shared goal setting and achievement of rehabilitation goals. Data from participants who responded to feedback questionnaires from the first 12 months of the service were analysed using descriptive statistics. Results: Ninety-five participants were sent feedback questionnaires with 31 responses received (33%). 96% of participants reported that they were satisfied with the service, with the same proportion expressing that they both felt they were treated with respect and dignity and that they had confidence and trust in the staff. All respondents felt that they could understand the answers to any questions they had while receiving rehabilitation and 92% of participants understood their rehabilitation goals, with 88% of participants feeling they achieved their rehabilitation goals. 88% of participants felt they were adequately involved in their care planning with 83% of participants feeling their family members had ample opportunity to ask questions during their rehabilitation experience. Results did not different by age group of patient or by time with the service. Conclusion: In this structured evaluation of the OPRAH team participants highly rated the service. Our results highlight that this integrated approach to care allowed patients to be involved in shared goal setting with the majority of patients satisfied that they achieved their goals.